Productivity and Nutrient Balance of Lentil- Mungbean -T. Aus - T. Aman Rice Cropping Pattern in High Barind Tract - Hossain, MS; Alam, SMM; Abida, MY; Hasan, MK; Khan, ASMMR (Bangladesh Agronomy Journal, 2018)
A field experiment viz. was conducted at farmers’ field of Field Service Research Division site, Kadamshahar, Godagari, Rajshahi under High Barind Tracts to evaluate the the effect of the intensive cropping on system productivity and economic returns as well as nutrient balance and changes in soil fertility of four crop-based cropping pattern Lentil –Mungbean -T.Aus -T.Aman during 2015-2016 and 2016-2017. The Lentil - Mungbean-T.Aus -T. Aman rice cropping pattern was considered as improved pattern (IP) and compared with the farmers’ practice (FP) of Boro - Fallow -T.Aman rice cropping pattern. The Lentil-Mungbean- T.Aus -T.Aman cropping pattern was involved with higher cultivation cost but having the higher rice equivalent yield (REY 15.01 t ha-1), gross return (Tk. 265500 ha-1), gross margin (Tk. 134750 ha-1) and marginal benefit-cost ratio (1.38). This cropping pattern gave 46% higher REY compared to the existing Boro-Fallow-T. Aman rice pattern. The four crop pattern took 345 days in a year for its cycle completion. Incorporation of legume residues into the soil in IP increased soil organic matter, total N, available P and Zn contents, as observed after two crop cycles. The IP increased N, P and K uptake by the crops in the sequence. The apparent balance, i.e. difference between inputs and outputs for N and K was negative. The apparent P balance was positive in IP while it was negative in FP. Therefore, it is concluded that the practicing Lentil- Mungbean-T.Aus-T.Aman rice cropping pattern is a productive and profitable system of production technology in the high Barind Tract. Bangladesh Agron. J. 2018, 21(1): 105-115